2014 IEEE PES General Meeting | Conference &Amp; Exposition 2014
DOI: 10.1109/pesgm.2014.6939403
|View full text |Cite
|
Sign up to set email alerts
|

On the convergence of relaxation schemes to couple phasor-mode and electromagnetic transients simulations

Abstract: Abstract-Hybrid simulations combining phasor-mode and electromagnetic transients models aim at taking advantage of computational speed of the former and accuracy of the latter. For simulation accuracy, a relaxation process is used, which consists of iterating between both models. The convergence properties of this relaxation process are investigated. The speed of convergence is assessed when the variables exchanged at the interface between both models are respectively pure voltage/current sources, Norton/Théve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…One issue tackled in this paper is the proper choice and update of the multi-port equivalent attached to those interface buses. This is an extension of the authors' previous work reported in [9], [10].…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…One issue tackled in this paper is the proper choice and update of the multi-port equivalent attached to those interface buses. This is an extension of the authors' previous work reported in [9], [10].…”
Section: Introductionsupporting
confidence: 85%
“…It was found that the conditions of type (a) did not make the iterations converge (even in steady-state conditions). All other boundary conditions led to convergence, and yielded the same dynamic response [9]. The performances of type (c) vary too much from one case to another; type (d) is consistently the best.…”
Section: Case 3: Tripping Of Generator G9mentioning
confidence: 88%
See 2 more Smart Citations
“…This assertion is supported by numerical results in [8], where the rate of convergence of the relaxation scheme is assessed under the assumption that the EMT and PM subsystem behave linearly.…”
Section: Simulationsmentioning
confidence: 77%